Making a home out of a resettlement housing a study on housing modifications in resettlement communities in Cagayan De Oro City - Sagrado, Sheryll Ann A.; Olalo, Kristin Faye M. (2023)
Resettlement in the Philippines have been one of the most widely known interventions to address the widespread displacements caused by natural disasters. A top-down approach in resettlement programs limits resident participation in formulating the design and policies, which leads to the users? needs to be unfulfilled and culture to be unconsidered. The manifestation of the dissatisfaction towards housing conditions is often exhibited through housing modifications. This descriptive and qualitative study determined the motivation and patterns for housing modifications in resettlement communities by dissecting the users? housing satisfaction in terms of socio-demographic and housing characteristics and distinguished whether modifications in the community over time played a significant role in the residents? satisfaction. The study was conducted in three resettlement communities in Cagayan de Oro City, each managed by different agencies. Data collection involved surveys, photo documentation, and mapping with site inspections. The satisfaction indices reveal that the residents have a high level of satisfaction towards the existing state of their modified homes. Hence, this reveals that their current satisfaction was achieved by their own initiative, reflecting a dissatisfaction towards the initial design of the core houses. Motivations for housing modification rely on the residents? existing socio-demographic characteristics. Four common typologies were also found which are roof extension, setback extension, horizontal division, and vertical extension. Management factors also play a significant role as it limits the level of modification to be pursued and no community modifications due to social action emerged but the present conditions of neighborhood facilities show that it needs improvement. Policy makers, architects, and allied professionals may use these results to improve resettlement housing programs wherein the adaptation process involved in undergoing resettlement is integrated and their culture and needs are considered.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2023